Effects of White Matter Hyperintensities on Verbal Fluency in Healthy Older Adults and MCI/AD - Kaskikallio, Alar; Karrasch, Mira; Koikkalainen, Juha; Lötjönen, Jyrki; Rinne, Juha O.; Tuokkola, Terhi; Parkkola, Riitta; Grönholm-Nyman, Petra (Frontiers in Aging Neuroscience, 2021)
Background: White matter hyperintensities (WMH) are markers for cerebrovascular pathology, which are frequently seen in patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD). Verbal fluency is often impaired especially in AD, but little research has been conducted concerning the specific effects of WMH on verbal fluency in MCI and AD. Objective: Our aim was to examine the relationship between WMH and verbal fluency in healthy old age and pathological aging (MCI/AD) using quantified MRI data. Methods: Measures for semantic and phonemic fluency as well as quantified MRI imaging data from a sample of 42 cognitively healthy older adults and 44 patients with MCI/AD (total n = 86) were utilized. Analyses were performed both using the total sample that contained 7 left-handed/ambidextrous participants, as well with a sample containing only right-handed participants (n = 79) in order to guard against possible confounding effects regarding language lateralization. Results: After controlling for age and education and adjusting for multiple correction, WMH in the bilateral frontal and parieto-occipital areas as well as the right temporal area were associated with semantic fluency in cognitively healthy and MCI/AD patients, but only in the models containing solely right-handed participants. Conclusions: The results indicate that white matter pathology in both frontal and parieto-occipital cerebral areas may have associations with impaired semantic fluency in right-handed older adults. However, elevated levels of WMH do not seem to be associated with cumulative effects on verbal fluency impairment in patients with MCI or AD. Further studies on the subject are needed.